Probiotic-based strategies for therapeutic and prophylactic use against multiple gastrointestinal diseases - Varankovich, Natallia V.; Nickerson, Michael T.; Korber, Darren R. (Frontiers in Microbiology, 2015)
Probiotic bacteria offer a number of potential health benefits when administered in sufficient amounts that in part include reducing the number of harmful organisms in the intestine, producing antimicrobial substances and stimulating the body's immune response. However, precisely elucidating the probiotic effect of a specific bacterium has been challenging due to the complexity of the gut’s microbial ecosystem and a lack of definitive means for its characterization. This review provides an overview of widely-used and recently-described probiotics, their impact on the human’s gut microflora as a preventative treatment of disease, human/animal models being used to help show efficacy, and discusses the potential use of probiotics in gastrointestinal diseases associated with antibiotic administration.